2007
DOI: 10.1161/hypertensionaha.106.086371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excessive Long-Term Exercise on Cardiac Function and Myocyte Remodeling in Hypertensive Heart Failure Rats

Abstract: Abstract-The long-term effects of exercise on cardiac function and myocyte remodeling in hypertension/progression of heart failure are poorly understood. We investigated whether exercise can attenuate pathological remodeling under hypertensive conditions. Fifteen female Spontaneously Hypertensive Heart Failure rats and 10 control rats were housed with running wheels beginning at 6 months of age. At 22 months of age, heart function of the trained rats was compared with heart function of age-matched sedentary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 39 publications
3
45
0
3
Order By: Relevance
“…While extreme levels of acute and chronic exercise may be deleterious to the heart by increasing apoptosis, �brosis, and ischemic dysfunction [62,113,114], moderate levels of exercise seem protective from cardiac damage. ese animal studies support the American College of Sports Medicine recommendation for encouragement of exercise on most, if not all, days of the week, at moderate intensities, by accumulating 30 minutes or greater of endurance-style physical activity [7].…”
Section: -Adrenergic Responsivenessmentioning
confidence: 99%
“…While extreme levels of acute and chronic exercise may be deleterious to the heart by increasing apoptosis, �brosis, and ischemic dysfunction [62,113,114], moderate levels of exercise seem protective from cardiac damage. ese animal studies support the American College of Sports Medicine recommendation for encouragement of exercise on most, if not all, days of the week, at moderate intensities, by accumulating 30 minutes or greater of endurance-style physical activity [7].…”
Section: -Adrenergic Responsivenessmentioning
confidence: 99%
“…This hypothesis is based on a small number of studies in rodents, which generally report that apoptosis is attenuated with training (9,15,16,20,39,40), with the caveat that no study to date has examined the impact of exercise training on cardiomyocyte proliferation in the spontaneously hypertensive rat (SHR) model. The importance of these questions is underscored by the recent report by Schultz et al (38), who showed that excessive levels of voluntary wheel running in aging spontaneously hypertensive heart failure rats increased myocardial fibrosis, worsened left ventricular (LV) function, and hastened the progression to heart failure. Thus the purpose of the present study was to determine how exercise training impacts myocardial remodeling in hypertension, specifically examining the relative roles of cardiomyocyte hypertrophy, apoptosis, and proliferation.…”
mentioning
confidence: 99%
“…10 In a previous study, chronic low-intensity aerobic exercise training (LIET) initiated during the late phase of compensated left ventricular hypertrophy delayed the onset of decompensated HF and reduced mortality in male SHHF rats. 11 Conversely, Schultz et al 12 reported recently that chronic voluntary wheel running accelerated pathologic left ventricular (LV) remodeling and increased HF mortality in female SHHF rats. This deleterious effect of voluntary exercise was attributed to the excessive volume and/or intensity of exercise achieved by animals in running wheels.…”
mentioning
confidence: 99%